Characterisation of the structure of ocr, the gene 0.3 protein of bacteriophage T7 - Atanasiu, C. (Oxford University Press, 2001)
The product of gene 0.3 of bacteriophage T7, ocr, is a potent inhibitor of type I DNA restriction and modification enzymes. We have used biophysical methods to examine the mass, stability, shape and surface charge distribution of ocr. Ocr is a dimeric protein with hydrodynamic behaviour equivalent to a prolate ellipsoid of axial ratio 4.3 ± 0.7:1 and mass of 27 kDa. The protein is resistant to denaturation but removal of the C-terminal region reduces stability substantially. Six amino acids, N4, D25, N43, D62, S68 and W94, are all located on the surface of the protein and N4 and S68 are also located at the interface between the two 116 amino acid monomers. Negatively charged amino acid side chains surround W94 but these side chains are not part of the highly acidic C-terminus after W94. Ocr is able to displace a short DNA duplex from the binding site of a type I enzyme with a dissociation constant of the order of 100 pM or better. These results suggest that ocr is of a suitable size and shape to effectively block the DNA binding site of a type I enzyme and has a large negatively charged patch on its surface. This charge distribution may be complementary to the charge distribution within the DNA binding site of type I DNA restriction and modification enzymes.